¿Adónde se habrá metido Mafiopoli? Las mafias italianas según La Gente d’Italia - Smeriglio, Gabriele Paolo (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
Generalisations can never tend to be exhaustive, nor can they claim to represent all subjectivities and the diverse and consequent political-ideological narratives that are part of them. But they also describe social and behavioural propensities present in the cultural folds of a specific social group. The role of newspapers, sounding boards for certain ethnic, political, economic and social sentiments, is fundamental to study the rapid consumption of these communicative processes whose contents end up being internalised even before they are processed. Beyond the level of scientific substance of which they are composed. In relation to the treatment of Italian mafias in the press, this manuscript aims to analyse, based on a selection of articles published between 2018 and 2022, the narratives produced by “La Gente d’Italia”, an Italian-language ethnic newspaper based in Uruguay, on the combination between persistence and change, between maintaining consolidated structures and adapting to the changes in the economic and social context in which the mafia is present today.